A Study of Theological Values in Sara Pataanguna Philosophy within Butonese Community Culture: An Islamic Religious Education Perspective - La Subu; Wardah Hanafie; Abdul Hakim Jurumiyah; Abdul Halik; Alwin Yasin (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2025)
This study examines the theological values embedded in the Sara Pataanguna philosophy of the Butonese people from the perspective of Islamic religious education. Using a qualitative case study design informed by anthropological and philosophical approaches, the research involved religious leaders, community figures, and traditional authorities as key informants. Data were collected through in-depth interviews and participant observation and analyzed using systematic qualitative procedures, including data reduction, data display, and conclusion drawing. The findings indicate that the theological values of Sara Pataanguna emphasize moral, ethical, and spiritual principles, as well as harmonious relationships among humans, God, and nature. These values are reflected in the daily lives of the Butonese community through cultural and religious practices, such as collective prayers, traditional rituals, and cooperative social activities that foster mutual assistance and respect. Furthermore, the study demonstrates that these theological values can be integrated into Islamic religious education through curriculum development, interactive pedagogical strategies, extracurricular programs, and teacher professional development. The study concludes that the integration of local theological values into Islamic religious education contributes to character development, cultural preservation, and the enhancement of educational relevance and quality. Abstrak: Penelitian ini bertujuan untuk mengkaji nilai-nilai teologis yang terkandung dalam filosofi Sara Pataanguna pada masyarakat Buton dari perspektif pendidikan agama Islam. Penelitian ini menggunakan pendekatan studi kasus kualitatif dengan perspektif antropologis dan filosofis. Informan utama terdiri atas tokoh agama, tokoh masyarakat, dan tokoh adat. Pengumpulan data dilakukan melalui wawancara mendalam dan observasi partisipatif, kemudian dianalisis menggunakan teknik reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa nilai-nilai teologis dalam Sara Pataanguna menekankan prinsip-prinsip moral, etika, dan spiritual, serta hubungan yang harmonis antara manusia, Tuhan, dan alam. Nilai-nilai tersebut diwujudkan dalam kehidupan sehari-hari masyarakat Buton melalui praktik budaya dan keagamaan, seperti doa bersama, ritual adat, serta aktivitas sosial gotong royong yang menumbuhkan sikap saling membantu dan menghormati. Lebih lanjut, penelitian ini menemukan bahwa nilai-nilai teologis tersebut dapat diintegrasikan ke dalam pendidikan agama Islam melalui pengembangan kurikulum, penerapan metode pembelajaran interaktif, kegiatan ekstrakurikuler, serta penguatan kompetensi guru. Penelitian ini menyimpulkan bahwa integrasi nilai-nilai teologis lokal dalam pendidikan agama Islam berkontribusi terhadap penguatan karakter, pelestarian budaya, serta peningkatan relevansi dan kualitas pendidikan.